Performance Evaluation of The Waterflooding System for Revitalizing Zombie Well “ZRC20” in a Heterogeneous Deltaic Reservoir at the “JE” Field - Refly Jayven Maarende; Teddy Kurniawan; Nuruddin Kafy El-Ridlo (Jurnal Global Ilmiah, 2026)
Oil fields that have been producing over extended periods generally experience gradual performance decline due to the depletion of natural reservoir energy, characterized by decreasing oil production rates, increasing water cut, and declining reservoir pressure until wells reach a depleted or inactive condition, commonly referred to as a zombie well. Well ZRC-20 in Field “JE,” operated by PT Pertamina Hulu Indonesia Regional 3 Zone 9 Sangatta Field, represents such a condition and is located within a layered heterogeneous deltaic reservoir. The characteristics of this deltaic reservoir, including lateral and vertical permeability variations and shale interbeds, create significant challenges for production management and enhanced oil recovery (EOR) implementation. This study aims to analyze the reservoir condition of Well ZRC-20, evaluate the performance of the mature well following Waterflooding injection, and assess the effectiveness of the existing Waterflooding system. The data used consisted of primary and secondary data from Sangatta Field, including production history, reservoir pressure, well log data, and injection data. The analysis was conducted using diagnostic methods, including the Inflow Performance Relationship (IPR), Hall Plot, Thakur’s Production Plot method, and Chan Plot, with an original oil in place (OOIP) of 999,000 STB and a recovery factor of approximately 33%. Following Waterflooding injection through the injection well, reservoir pressure and oil production rates increased. However, further evaluation identified several technical issues limiting the effectiveness of the system, including early water breakthrough, near-wellbore channeling indicated by Chan Plot analysis, and declining injection well injectivity as demonstrated by the Hall Plot. Overall, Waterflooding positively influenced production performance but still requires further optimization through injection rate management, channeling control, and adjustment of the injection pattern to better accommodate the characteristics of the heterogeneous deltaic reservoir.